2023
DOI: 10.1002/oby.23745
|View full text |Cite
|
Sign up to set email alerts
|

Senescence markers in subcutaneous preadipocytes differ in childhood‐ versus adult‐onset obesity before and after weight loss

Abstract: Objective The aim of this study was to determine the effect of age of obesity onset on senescence‐related markers in abdominal (AB) and femoral (FEM) subcutaneous adipose tissue (SAT) before and after moderate (~10%) weight loss. Methods AB and FEM SAT were collected from human females with childhood‐onset obesity (CO) or adult‐onset obesity (AO) before and after diet‐ and exercise‐induced weight loss. Immunofluorescence analysis of γH2AX/RAD51 (DNA damage/repair markers) and p53/p21 (senescence markers) was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Recently, it was reported that preadipocytes isolated from abdominal and femoral subcutaneous adipose tissue explants of women with childhoodonset obesity had higher levels of damaged DNA and more senescent cells (assessed as p53þ/p21þ cells) than preadipocytes isolated from women with adult-onset obesity [19]. After moderate (10%) weight loss, DNA damage decreased in all studied patients and no difference between groups was recognized.…”
Section: Adiposity Dna Damage and Cell Senescencementioning
confidence: 82%
“…Recently, it was reported that preadipocytes isolated from abdominal and femoral subcutaneous adipose tissue explants of women with childhoodonset obesity had higher levels of damaged DNA and more senescent cells (assessed as p53þ/p21þ cells) than preadipocytes isolated from women with adult-onset obesity [19]. After moderate (10%) weight loss, DNA damage decreased in all studied patients and no difference between groups was recognized.…”
Section: Adiposity Dna Damage and Cell Senescencementioning
confidence: 82%
“…Two important tumor suppressor pathways, p16 ink4a ‐pRb and p53‐p21, are engaged to initiate and maintain persistent cell cycle arrest in senescence. 68 , 72 , 73 These four crucial factors can induce senescence by prolonged overexpression of any one of them, and they essentially sustain the senescent state by causing extensive alterations in gene expression through p53, which is an important transcription factor, and Rb, which participates in regulating the expression of a variety of genes. 74 The Rb family is a primary target of cyclin–CDK complexes, and it functions by sequestering E2F complexes and thus inhibiting the expression of E2F target genes.…”
Section: Morphological Features Of Senescence and Their Role In Tumor...mentioning
confidence: 99%